PEMAHAMAN KONSEP SISWA PADA PEMECAHAN MASALAH SOAL GEOMETRI POKOK BAHASAN SEGIEMPAT DITINJAU DARI GAYA KOGNITIF REFLEKTIF-IMPULSIF SISWA - Trapsilasiwi, Dinawati; Jhahro, Kholif Fatujs; Setiawan, Toto Bara (Department of Mathematics Education , University of Jember, 2018)
This study to describe the understanding of students 'concepts on problem solving about the geometry of the quadrilateral subject matter in terms of the students' impulsive reflective cognitive style in SMP Negeri 7 Jember. The descriptions of this study were carried out by providing an overview of reflective cognitive-style students and students with impulsive cognitive styles. Based on the results of data analysis and discussion, students with reflective cognitive style are able to understand the problem, plan the settlement, solve the problem, and correct it again. As for impulsive students not understanding the problem, unable to plan the settlement, unable to solve the problem, and unable to correct again. Keywords: Understanding of Concepts, problem solving, cognitive style, reflective, impulsive.